2021
DOI: 10.1021/acs.jpcb.1c06520
|View full text |Cite
|
Sign up to set email alerts
|

Controlled DNA Delivery Using Poly(lactide) Nanoparticles and Understanding the Binding Interactions

Abstract: Cationic polymer-based gene delivery vectors suffer from several limitations such as low DNA-loading capacity, poor transfection, toxicity, environmental degradations, etc. Again, very limited works are available addressing the binding interactions in detail at the atomic level explaining the loading capacity, protection ability against harsh environments, and controlled release behavior of the DNA-encapsulated vehicles. Here, a poly(L-lactide) (PLA) nanoparticle-based controlled DNA release system is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Overall, terpolymer-based NCs, thanks to their composition and hollow structure, represent a delivery system capable of enhancing the amount of encapsulated DNA, as well as leading to a more prolonged release over time. Indeed, many polymeric drug delivery systems have been investigated for the delivery of nucleic acid; however, the loading of DNA is often lower than 50% with a fast release in the order of hours [66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, terpolymer-based NCs, thanks to their composition and hollow structure, represent a delivery system capable of enhancing the amount of encapsulated DNA, as well as leading to a more prolonged release over time. Indeed, many polymeric drug delivery systems have been investigated for the delivery of nucleic acid; however, the loading of DNA is often lower than 50% with a fast release in the order of hours [66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Material scientists must consider opting for materials that have a short life in the biological milieu and that degrade into easy-tometabolize components, especially in the context of intravenous injections (like polylactide, polyglycolide). [15][16][17][18] In this respect, it has been recently observed that the human body can perform even drastic degradation, digesting both "unbreakable" (e.g., carbon nanotubes) and biologically inert (PEO) materials. [19][20][21] Nevertheless, we will focus on the issues concerning the "potential" toxicity of the NPs, discussing specifically which analytical approaches should be used, and further implemented, to address their safety.…”
Section: Preliminary Considerations On Nps' Toxicitymentioning
confidence: 99%
“…It is thus not surprising why biomaterial scientists are reluctant to synthesize new materials, as scientists prefer to use already established clinically‐safe ones. Material scientists must consider opting for materials that have a short life in the biological milieu and that degrade into easy‐to‐metabolize components, especially in the context of intravenous injections (like polylactide, polyglycolide) 15–18 . In this respect, it has been recently observed that the human body can perform even drastic degradation, digesting both “unbreakable” (e.g., carbon nanotubes) and biologically inert (PEO) materials 19–21 …”
Section: The Journey Of Nps Within the Bodymentioning
confidence: 99%
“…Furthermore, Leuprolide induced PDLA crystallisation in a less stable crystal phase (β-phase) that recrystallises into the α-phase upon further heating [187]. DNA-loaded PLA [188] as well as PLA-PEG [189,190] nanoparticles were also recently developed, where DNA acts as a nucleating agent due to the strong interactions between PLA/DNA molecules, promoting the crystallisation of PLA nanoparticles, which is primarily responsible for the sustained release of DNA. In addition, the DNA melting point shifted to a higher temperature in the PLA-DNA complex, suggesting the good protecting ability of the PLA matrix towards the incorporated DNA.…”
Section: Chiral Drugsmentioning
confidence: 99%